MICROTEACHING TO TRAINING OF TEACHING ABILITY FOR TEACHER CANDIDATE; A STUDY OF HISTORICAL TO STRAIGHTEN FOR THE IDEAL CONCEPT OF EDUCATION AND TEACHER-TRAINING OF ART TEACHER - Yos Sudarman (International Conference on Languages and Arts, 2015)
This paper wants to explain again how the actual implementation on training of teaching for teacher candidate through microteaching activities in LPTK (Lembaga Pendidikan Tenaga Kependidikan). For all these purposes, one of the ways that could be followed in order to find the actual concept of microteaching, is to tracing back the history of the development of microteaching itself, especially since it was first discovered by analyst the field of applied science in US to continue to be used in education and learning-instructional today. From the search results, it is expected that readers, especially from lecturers and teachers became understand, that the microteaching applied in LPTK , including Art-LPTK , at present there are still retains the conventional microteaching model, and partially update it. What updates forms microteaching model that developed in the most of LPTK ’s today, has significant contributed towards for improving the quality of teacher candidates? Or, whether the use of conventional microteaching model that is actually still maintain quality characteristics for training of teaching for teacher candidate in LPTK ? Based on an assumption, that conventional microteaching model is still based on the concept of behaviorist, may be the microteaching which is still relevant to current developments on creating teacher candidate who are professionals in their diciplines.